Hubungan antara Jumlah Kehilangan Gigi dengan Status Gizi pada Lansia di Desa Kolongan Atas II Kecamatan Sonder - Pioh, Charlene; Siagian, Krista V.; Tendean, Lydia (e-GiGi, 2018)
Abstract: Tooth loss is commonly found among elderly and have bad impact on the TMJ, mastication, aesthetics as well as speech function. Due to mastication disorder, the elderly tend to choose certain food which influences their nutritional status. This study was aimed to obtain the relationship between tooth loss and nutritional status based on BMI among the elderly at Kolongan Atas II, Sonder. This was an analytical descriptive study with a cross-sectional design. Population included elderly aged 60-65 years old at Kolongan Atas II, Sonder. Samples were obtained by using total sampling method. The results showed that there were 30 elderlies that fulfilled the inclusion criteria. Tooth loss more than ten teeth was most common among elderly with normal nutritional status followed by those with overweight. Meanwhile, there was no elderly with underweight. The relationship between the tooth loss and nutritional status was tested with the chi-square which resulted in P value of 0.597. Conclusion: There was no significant relationship between tooth loss and nutritional status among elderly at Kolongan Atas II, Sonder. The elderlies were advised to pay attention to their nutritional status and to use dentures for replacement of their missing teeth.Keywords: tooth loss, nutrient status, elderlyÂ Abstrak: Pada masa lansia sering terjadi kehilangan gigi yang menyebabkan gangguan TMJ, pengunyahan, estetik, dan fungsi bicara. Gangguan pengunyahan pada lansia menyebabkan kecenderungan memilih makanan tertentu yang dapat memengaruhi status gizi. Penelitian ini bertujuan untuk mengetahui hubungan antara kehilangan gigi dengan status gizi berdasarkan IMT pada lansia di Desa Kolongan Atas II Kecamatan Sonder. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang. Populasi penelitian ialah lansia berusia 60-65 tahun di Desa Kolongan Atas II Kecamatan Sonder sedangkan sampel diperoleh menggunakan metode total sampling. Hasil penelitian mendapatkan sebanyak 30 responden yang memenuhi kriteria inklusi. Kehilangan gigi >10 gigi terbanyak pada lansia dengan gizi normal diikuti dengan gizi lebih. Tidak didapatkan lansia dengan gizi kurang. Hubungan antara kehilangan gigi dengan status gizi berdasarkan IMT diuji dengan uji chi square dan mendapatkan nilai P=0,597. Simpulan: Tidak terdapat hubungan bermakna antara kehilangan gigi dengan status gizi pada lansia di Desa Kolongan Atas II Kecamatan Sonder. Disarankan agar para lansia untuk tetap memperhatikan asupan makanan agar dapat mempertahankan status gizi yang baik dan menggunakan gigi tiruan sebagai pengganti gigi yang hilang.Kata kunci: kehilangan gigi, status gizi, lansia